Simulation of Groundwater Potential Zone Using Geographic Information System (GIS) Through Related Factors - Olusami, Joel Olusoji; Familusi, Ayokunle Oluwaseun; Olatunji, Abass Adekunle; Ogundare, Damilola Ayodele; Akindele, Akinsanya Ebenezer; Akinyele, Isikilu Oyewole (Analecta Technica Szegedinensia, 2024)
ABSTRACT Groundwater is the primary water source for irrigating and drinking in dry seasons. This work was examined to assess groundwater potential area underlain by basement complex with GIS based approach of selected locations in Osogbo. The soil samples were taken and soil textural and permeability analyses were done in the laboratory. Supervised classification analysis was done on LandSAT imagery to generate Land use and a lineament map, surface analyst algorithm was applied on ASTER dam to generate elevation map. Hydraulic conductivity and overburden thickness maps were generated from the Borehole data parameters. Interpolation method was used to generate spatially spread clay, silt, sand, rainfall and hydraulic conductivity. Multi-criteria analysis was used to generate groundwater potential zone map in the study area. Specific factors were considered for groundwater potential zone. Reclassification was done on each of the considered factors and AHP model was used to assign weight to all the factors. The results of the various factors responsible for groundwater potential include lineament density 0-0.0028; sand 67.2-89.60%, silt 9.00-30.00%, clay 0.17-2.80%, permeability 0.000010-0.00002, rainfall 1304.02-1469.06mm/yr, hydraulic conductivity 0.21-0.96m/min, land use consisting of degraded forest 48.65%, riparian forest 13.05%, built up 38.29%, and water body 0.001%. However, ground water potential of the study area was assessed and classified into fair, good and very good with the coverage of 2%, 80% and 18% respectively. Conclusively, the groundwater recharge potential is very good at Ofatedo, Gbonmi and Oke-Oro locations, good at Awosuru, Gbodofon and Dagbolu locations, but fair at Mallam Tope location in Osogbo